Adaptação curricular em atividades de leitura e escrita para alunos com deficiência intelectual na perspectiva colaborativa - Muniz, Joice Daiane (Universidade Federal de São Carlos, 2019)
The inclusion of students with intellectual deficiency is not only due to enrollment in the regular school system, but also to the guarantee of permanence and effective learning. Given this, there is a direction of actions for the school that can create and organize practices capable of effectively learning the school contents. In this sense, the general objective of the research was to evaluate adaptations in reading and writing content for students with intellectual deficiency in the collaborative perspective, while the specific objectives were: (a) characterize a pedagogical practice implemented by the teacher; (b) verify the profile of class students in reading and writing performance; (c) elaborate and apply a reading and writing intervention proposal based on the collaborative model and (d) check the effectiveness of the intervention proposal. The study included the teacher of the 2nd grade of Elementary School and her students, one of them with an intellectual deficiency report and her mother. The study was characterized as a collaborative research with qualitative focus. For this, a data collection happened in a state public school of the medium-sized city in the interior of the state of São Paulo-SP. To achieve the proposed objectives, the participants answered: (a) a semi-structured interview script for the teacher; (b) School Performance Test - SPT for students; (c) Interview script for the mother; (d) roadmap for an intervention proposal; (e) an intervention proposal evaluation questionnaire. Qualitative analysis was performed through the elaboration of categories, with the data obtained in the analyzes, as well as interviews and quantitative and qualitative analyzes with the data obtained through the School Performance Test – SPT. As for the results, it was found that the teacher encouraged the participation of students in class and that she was aware that the student with intellectual deficiency needed individualized attention, as well as different adaptations in the content worked and the way of teaching. It is still possible that the teacher does not make these adaptations for students with intellectual deficiency, because there is a parallel demand to the other students in the class. School performance in reading and writing skills showed that all students were at the same level, according to the School Performance Test - SPT. Respect for the elaboration of adapted curricular activities, was visible or the involvement of the teacher in all the meetings, as well as the planning of activities for the teaching and learning process of students with intellectual deficiency in the ability for reading and writing. In the evaluation procedure of the intervention proposal, it was noticed the participation of students with intellectual deficiency in classes and activities with greater autonomy and involvement. It was concluded, therefore, that these are recommended actions for in-service training for teachers on how to contemplate their curriculum adaptation planning to support the inclusion of students with intellectual deficiency.
Curriculum adaptation in reading and writing activities for students with intellectual deficiency in the collaborative perspective.
Keywords: Educação Especial; Adaptação curricular; Deficiência intelectual; Leitura e escrita; Ensino colaborativo; Special education; Curriculum adaptation; Intellectual deficiency; Reading and writing; Collaborative teaching; CIENCIAS HUMANAS::EDUCACAO